Design and Construction of an IoT-Based Coconut Milk Processing Machine to Become VCO - Mahmud Idris; Yudhi Agussationo; Sandi Yudha Barri Zaqy (Jurnal INOVATOR, 2025)
Virgin Coconut Oil (VCO) is a processed product from coconut flesh in the form of a clear, tasteless liquid with a distinctive coconut aroma. VCO is obtained through processing coconut milk with several methods, namely the gradual cooking method, the oil fishing method, and the fermentation method. Of these three methods, gradual heating is the most commonly used. This process requires a stable heating device to produce quality VCO. Therefore, to maintain the stability of the heating, precise control is required in the gradual heating method. The heating device is designed to streamline the processing process with an IoT-based control system. This VCO processing device is designed with a temperature control system using an NTC sensor with a high accuracy of ±1.5°C to ensure temperature stability during the coconut milk heating process using a dual-core ESP32 microcontroller that has WiFi connectivity features, thus enabling integration into the Internet of Things (IoT) system for remote monitoring. For the heating process, this device is equipped with a 220V 400W heating element controlled by a Solid State Relay (SSR), so that the temperature can be precisely controlled in the range of 60–90°C.